ANALYSIS OF LOCAL WISDOM IN SCIENCE LEARNING: PEDAGOGICAL APPROACH AT SDN 64, AIR TEMAM VILLAGE, LUBUKLINGGAU SELATAN 1 DISTRICT, LUBUKLINGGAU CITY - Onky Paramanda Arma; Iis Siti Aisyah; Lud Waluyo (RADJA PUBLIKA, 2025)
This study aims to explore the integration of local wisdom in Natural Science (IPA) learning at SDN 64 Kelurahan Air Temam, Lubuklinggau. Using a qualitative approach and case study, this study involved fifth grade students as subjects to understand their perceptions of learning that integrates local wisdom. Data were collected through questionnaires, interviews, observations, and analysis of curriculum documents. The results showed that the integration of local wisdom not only increased students' interest and motivation, but also deepened their understanding of scientific concepts. This study is expected to contribute to the development of learning methods that are more relevant and responsive to local culture, as well as being the basis for educational policies that are more oriented towards local wisdom.